Origin of carbonate-silicate rocks of the Porya Guba (the Lapland-Kolvitsa Granulite Belt) revealed by stable isotope analysis (δ18O, δ13C) - Dmitrii P. Krylov; Ekaterina V. Klimova (Записки Горного института, 2024)
Carbonate-silicate rocks of unclear origin have been observed in granulites of the Porya Guba of the Lapland-Kolvitsa Belt within the Fennoscandinavian Shield. The present work aims to reconstruct possible protoliths and conditions of metamorphic transformation of these rocks based on oxygen and carbon isotopic ratios combined with phase equilibria modeling. Isotope analysis and lithochemical reconstructions suggest that carbonate-silicate rocks of the Porya Guba represent metamorphosed sediments (possibly marls) with the isotopic composition corresponding to the Precambrian diagenetically transformed carbonates (δ18O ≈ 17.9 ‰, SMOW and δ13C ≈ –3.4 ‰, PDB). The chemical composition varies depending on the balance among the carbonate, clay, and clastic components. Significant changes of the isotopic composition during metamorphism are caused by decomposition reactions of primary carbonates (dolomite, siderite, and ankerite) producing CO2 followed by degassing. These reactions are accompanied by δ18O and δ13C decrease of calcite in isotopic equilibrium with CO2 down to 15 ‰ (SMOW) and –6 ‰ (PDB), respectively. The isotopic composition is buffered by local reactions within individual rock varieties, thus excluding any pronounced influence of magmatic and/or metasomatic processes.